2018
DOI: 10.1097/mnm.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT in evaluating molecular subtypes and clinicopathological features of primary breast cancer

Abstract: Increased primary tumor F-FDG uptake was associated with aggressive molecular subtypes in this study. The relationship of distant nodal and organ metastasis with primary tumor SUVmax showed that increased F-FDG uptake is important in terms of management of therapy and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
8
14
0
3
Order By: Relevance
“…8 In our previous study, we found significant association between 18F-FDG SUV max value and tumour stage, ER-PR expression, LN involvement and DOM in BC. 2 In the present study, increased SUV max showed statistically significant association with increased tumour diameter (>2 cm), high Ki-67 (>15%), and DOM. There was also significant association between molecular subtypes and SUV max .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…8 In our previous study, we found significant association between 18F-FDG SUV max value and tumour stage, ER-PR expression, LN involvement and DOM in BC. 2 In the present study, increased SUV max showed statistically significant association with increased tumour diameter (>2 cm), high Ki-67 (>15%), and DOM. There was also significant association between molecular subtypes and SUV max .…”
Section: Discussionsupporting
confidence: 59%
“…18F‐fluoro‐2‐deoxy‐glucose positron emission tomography/computed tomography (18F‐FDG PET/CT) has proven predictive in value for BC staging/re‐staging. It is also valuable for evaluating treatment response with assessment of regional LN involvement, distant metastasis and recurrence 2,3 . However, the method has some known technical and patient‐related limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies demonstrated that the higher 18 F-FDG uptake of the primary breast lesion could mean a higher incidence of ALN metastasis (8,(34)(35)(36). Other studies however revealed no signi cant difference between MALN and BALN in terms of primary breast mass in 18 F-FDG PET/CT (37,38), which was also found in the present study for both 18 There are some limitations in the present study. Particularly, the number of cases is not large enough.…”
Section: Semi-quantitative Assessment Findingssupporting
confidence: 62%
“…Additionally, PET/ CT is clinically indicated only for stage III breast cancer patients and so stage I and II breast cancers, which represent the majority, have been excluded from the analysis of these retrospective datasets. Radiogenomic analyses to date have principally focused on metabolic activity parameters of the primary tumor, most commonly via analysis of the maximum standardized uptake values, but also via analysis of the metabolic tumor volume and total lesion glycolysis (30)(31)(32)(33)(34)(35)(36)(37)(38)(39). While more advanced metrics such as histogram-based features have only recently been explored (30).…”
Section: Fdg Pet/ctmentioning
confidence: 99%